№1 Раскройте скобки и упростите полученное выражение: а) -(х-8)+(40-х)= б) 12х-4*(6х+7)= №2 Решите уравнение: а) 7а+63=0 б) 15у-20=6+2у
№1 Раскройте скобки и упростите полученное выражение:
а) -(х-8)+(40-х)=
б) 12х-4*(6х+7)=
№2 Решите уравнение:
а) 7а+63=0
б) 15у-20=6+2у
Ответ(ы) на вопрос:
Гость
а) -(х-8)+(40-х)= -x+8+40-x=-2x+48=48-2x
=================================
б) 12х-4*(6х+7)= 12x-24x-28=-12x-28=-(12x+28)
=================================
а) 7а+63=0
7a=-63
a=-63/7
a=-9
Ответ: а=-9
=================================
б) 15у-20=6+2у
15y-20=6+2y
15y-2y=6+20
13y=26
y=26/13
y=2
Ответ: у=2
Гость
а)-(х-8)+(40-х).=-х+8+40-х=-2х+48=-2*(х-24). б)12х-4*(6х+7). 12х-24х-28=-12х-28 решить уравнение. 7а+63=0. 7а=-63:(7) а=-9. б)15у-20=6+2у. 15у-2у=20+6. 13у=26:(13) у=2.
Не нашли ответ?
Похожие вопросы